Collaboration of Pancasila and Civic Education Teachers and Guidance Counseling Teachers in the Developing of Student Characters in Senior High School (JED (Jurnal Etika Demokrasi), 2020)
Abstract. This article aims to establish the collaboration between the Pancasila and Civic Education teacher and the Guidance Counseling teacher in developing the character of students in high school. This article is the result of a descriptive qualitative research study by selecting informants using the purposive sampling method. Data collection techniques used were observation, interviews, and documentation. Data were analyzed through data reduction steps and conclusion drawing. The technique for checking the validity of the data is the triangulation of sources. The results showed that the formation of students' character in the school could be carried out optimally if the teacher especially the Pancasila and Civic Education teacher collaborated with the Guidance Counseling teacher. Collaboration is carried out in the form of assignments for the preparation of student activity journals assigned by Pancasila and Civic Education teachers. The activity journal is prepared based on the Guidance Counseling teacher's input after the students conduct counseling related to the reported activity. Through these activity journals, the Pancasila and Civic Education teacher can identify obstacles in character formation and then look for solutions together with the Guidance Counseling teacher.Keywords: Teacher Collaboration,Civic Education, Guidance Counseling, CharacterAbstrak.  Artikel ini bertujuan untuk mengungkapkan kolaborasi yang dilakukan guru Pendidikan Pancasila dan Kewarganegaraan dan Guru Bimbingan Konseling dalam pembentukan karakter siswa di SMA. Artikel ini merupakan hasil kajian penelitian kualitatif deskriptif dengan pemilihan informan menggunakan metode pusposive sampling. Teknik pengumpulan data yang digunakan adalah observasi, wawancara dan dokumentasi. Data dianalisis melalui langkah-langkah reduksi data dan penarikan kesimpulan. Teknik pemeriksaan keabsahan data dilakukan dengan triangulasi sumber. Hasil penelitian menunjukkan bahwa pembentukan karakter siswa di Sekolah dapat terlaksana secara optimal jika guru khususnya guru Pendidikan Pancasila dan Kewarganegaraan melakukan kolaborasi dengan guru Bimbingan Konseling. Kolaborasi dilakukan dalam bentuk pemberian penugasan penyusunan jurnal aktivitas siswa yang ditugaskan oleh guru Pendidikan Pancasila dan Kewarganegaraan. Jurnal aktivitas tersebut disusun berdasarkan masukan guru Bimbingan Konseling setelah siswa melakukan konseling terkait aktivitas yang dilaporkannya. Melalui jurnal aktivitas tersebut guru Pendidikan Pancasila dan Kewarganegaraan dapat mengidentifikasi hambatan dalam pembetukan karakter dan kemudian mencari solusi Bersama dengan guru Bimbingan Konseling.Kata Kunci: Kolaborasi Guru, Pendidikan Pancasila dan Kewarganegaraan, Bimbingan dan Konseling, Karakter